Recurrence Rate of Pleomorphic Adenoma in Minor Salivary Glands After Surgical Excision: A Retrospective Clinical Study - Abbas, Ali Hussein; Al-Khannaq, Yassir Ryadh; Al-Anee , Auday Mahmood; Al-Quisi, Ahmed Fadhel (Al-Rafidain Journal of Medical Sciences ( ISSN 2789-3219 ), 2024)
Background: Pleomorphic adenoma of the minor salivary gland is a rare benign tumor. It commonly occurs in the hard and soft palates. Treatment by surgical excision achieved success in improving the patient’s health. Objective: To evaluate the recurrence rate after surgical treatment of pleomorphic adenoma in minor salivary glands. Methods: This retrospective study included patients who attended the Maxillofacial Surgery Unit in Ghazi Al-Hariri Hospital, Baghdad, from 2019 to 2021, complaining of soft tissue lumps involving the soft and hard palate, buccal mucosa, and upper lip. After the provisional diagnosis of these lesions, a total surgical excision of the tumor with a safe margin of 1 mm was performed, and the biopsy was sent for histopathological examination. A follow-up evaluation was performed for all patients two years after surgery. Results: Twenty-three patient data sheets with minor salivary gland pleomorphic adenoma were screened and initially included in this study. Only 12 patients (8 males and 4 females) were eligible, and 11 were excluded. Out of the patients who had total surgical excision, two women experienced tumor recurrence during the follow-up period. One had an ulcerated pleomorphic adenoma in the hard palate, and the other had a pleomorphic adenoma in the soft palate with mucosal tethering. Conclusions: Wide surgical excision is a successful treatment to decrease the recurrence rate, especially in cases of ulceration and tethering.